Home. - Graham, Ian (Mankato, Minn : QEB pub, 2008)
"Tells the history of inventions that changed the home, from electricity and light bulbs to refrigerators, home computers, and home video game systems"--Provided by publisher.
Contents: Inventions in your home -- Lighting up -- Button up -- Home help -- Tick tock -- Food matters -- Tin tops -- Pocket power -- Music machines -- Home computers -- On the box -- Playing games -- Eco-homes -- Glossary. Notes: Includes index.
Keywords: Household appliances --United States --History --Juvenile literature